The Blackwell Cultural Economy Reader. - Amin, Ash (Blackwell readers in geography., 2007)
This Reader brings together the exciting and innovative work that has appeared in the last 10 years in the growing field of cultural economy.:.; Brings together exciting and innovative work from the last ten years in the emerging field of cultural economy.; Contains a substantial introduction by the editors on the main strands and history of the cultural economy approach.; Shows how the pursuit of prosperity always involves multiple and hybrid orderings that cannot be reduced to either the terms culture or economy.; Shows that thinking about cultural economy is both a substantive task and a va.